Load Flow Analysis of the Nigerian Transmission Grid Using DIgSILENT PowerFactory - Omowumi Olasunkanmi (2021 56th International Universities Power Engineering Conference (UPEC), 2021)
The subject of this work is the development of a load flow model for the Nigerian 330 kV transmission system. The model has been developed in DIgSILENT PowerFactory based on data provided by the Nigerian Electricity system operator (NESO). Two scenarios (summer and winter) were considered: for each scenario, load data, generator data, and transmission line parameters were used as inputs to the model. The voltage profiles resulting from the load flow were compared with the original data, and some discrepancies were found. Assumptions and modifications were made to achieve load flow results that were closer to the system data. The results show that in summer and winter, power generated was 4804.10 MW and 4394.41 MW, respectively. The bus voltages were within the voltage magnitude of 0.85 pu and 1.05 pu, according to the local grid code. The model documented in this paper will be used as a baseline for reliability and stability studies. This research aims to identify potential reinforcements to the 330 kV Nigerian transmission system to meet future electricity demand.